2023
DOI: 10.3390/ani14010077
|View full text |Cite
|
Sign up to set email alerts
|

Thyme, Oregano, and Garlic Essential Oils and Their Main Active Compounds Influence Eimeria tenella Intracellular Development

Martina Felici,
Benedetta Tugnoli,
Callum De Hoest-Thompson
et al.

Abstract: Coccidiosis poses a significant challenge in poultry production and is typically managed with ionophores and chemical anticoccidials. However, the emergence of drug resistance and limitations on their use have encouraged the exploration of alternative solutions, including botanical compounds and improvements in in vitro screening methods. Prior research focused only on the impact of these alternatives on Eimeria invasion, with intracellular development in cell cultures receiving limited attention. This study a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The beneficial effects of these PFAs include supporting the host by immunomodulatory effects and providing protection against free radicals by scavenging reactive oxygen species and interfering directly with parasitic metabolism, reducing oocyst shedding and cecal short-chain fatty acid production [45,163,165]. Furthermore, Felici et al (2023) [166] reported that bioactive compounds from a PFA can inhibit the intracellular replication of Eimeria and reduce schizont numbers.…”
Section: Role Of Phytogenic Feed Additivesmentioning
confidence: 99%
“…The beneficial effects of these PFAs include supporting the host by immunomodulatory effects and providing protection against free radicals by scavenging reactive oxygen species and interfering directly with parasitic metabolism, reducing oocyst shedding and cecal short-chain fatty acid production [45,163,165]. Furthermore, Felici et al (2023) [166] reported that bioactive compounds from a PFA can inhibit the intracellular replication of Eimeria and reduce schizont numbers.…”
Section: Role Of Phytogenic Feed Additivesmentioning
confidence: 99%